Occupational burnout and its causes among practicing nurses in hospitals affiliated to Babol University of Medical Sciences, 2004 - P Aziz Nejad (Babol University of Medical Sciences, 2006)
BACKGROUND AND OBJECTIVE: Occupational burnout is a common problem among nurses that can have negative effects on patient care and physical and mental health status of nurses. It imposes some treatment and personnel expenses. The purpose of this study was to evaluate the prevalence and causes of occupational burnout in practicing nurses in hospitals of Babol University of medical sciences. METHODS: Research resourses in this study was nursing staff who working in hospitals of Babol University of Medical Sciences. Data were collected by a questionnaire that included 11 questions about personal characteristics, 40 questions about Galdard occupational burnout and 20 questions about causes of occupational burnout. Score classification of Galdard occupational burnout were as follows: occupational burnout level in scores (40-80), (81-120), (121-200) and (201-280) was very low, low, high and very high, respectively. FINDINGS: In this study, 30.7% of cases had low level of occupational burnout, 68.6% had high level of occupational burnout and 0.7% had very high level of occupational burnout. Also, the staff of Pediatric hospital (82.9%) had the highest level of occupational burnout. There was a significant relationship between occupational burnout and the age of staff (p=0.01) and their years of working (p=0.03). The most important causes of occupational burnout were: low amount of salary and perks (93.9%), lack of social support (85.5%), lack of management support (85%), lack of job security (84%) and high working hours (83.3%). CONCLUSION: Occupational burnout is a common problem among helping professions. In such a situation, the nursing managers should provide conditions to reduce the staff psychological stress such as increasing their salary, decreasing the working hours, setting recreational plans, group working, participating in meetings to solve the problems, holding sports classes and educational workshops to cope with stress.